Surface-engineered liposomal particles of calcium ascorbate with fenugreek galactomannan enhanced the oral bioavailability of ascorbic acid: a randomized, double-blinded, 3-sequence, crossover study. Issue 60 (26th November 2021) - Joseph, Ashil; Kumar, Dinesh; Balakrishnan, Abhilash; Shanmughan, Prasanth; Maliakel, Balu; IM, Krishnakumar
Abstract : A green process to modulate the surface properties of liposome was reported using fenugreek galactomannan hydrogel and successfully applied to vitamin C with significant enhancement in human oral bioavailability. Abstract : The antioxidant, anti-inflammatory, immunomodulating, anti-thrombotic, and antiviral effects along with its protective effects against respiratory infections have generated a great interest in vitamin C (vitC) as an attractive functional/nutraceutical ingredient for the management of COVID-19. However, the oral bioavailability and pharmacokinetics of vitC have been shown to be complex and exhibit dose-dependent non-linear kinetics. Though sustained-release forms and liquid liposomal formulations have been developed, only marginal enhancement was observed in bioavailability. Here we report a novel surface-engineered liposomal formulation of calcium ascorbate (CAAS), using fenugreek galactomannan hydrogel in powder form, and its pharmacokinetics following a randomized, double-blinded, single-dose, 3-way crossover study on healthy human volunteers ( n = 14). The physicochemical characterization and in vitro release studies revealed the uniform impregnation of CAAS liposomes within the pockets created by the sterically hindered galactomannan network as multilaminar liposomal vesicles with good encapsulation efficiency (>90%) and their stability and sustained-release under gastrointestinal pH conditions. Further human studies demonstrated >7-fold enhancement in the oral bioavailability of ascorbate with a significant improvement in pharmacokinetic properties ( C max, T max, T 1/2, and AUC), compared to the unformulated counterpart (UF-CAAS) when supplemented at an equivalent dose of 400 mg of CAAS as tablets and capsules.